WHAT IS NEW MEDIA? TEN YEARS AFTER THE LANGUAGE OF NEW MEDIA. - Galloway, Alexander R. (Criticism)
A literary criticism of the book "The Language of New Media," by Lev Manovich is presented. It explores the cultural significance of the book and its aim to reflect upon the development of software and Internet culture. An overview of several of the books central ideas are presented including the idea that cinema was the first new media and observations on the future of open interfaces.